Caracterización de madres que viven con el virus VIH/SIDA. - Rodríguez Artavia, Allan (2010)
This article presents the main characteristics of mothers living with the virus infection of HIV/SIDA and attend to the "Living Hope Women's Association. The research is quantitative, descriptive; information was obtained from a self-administered questionnaire. The results found that, when interacting in organized groups, users are more receptive to their health status to acquire an empowerment that helps them deal with the social environment; on the other hand, socially there, including the health sector, a feeling of rejection people with HIV infection, behavior which is manifested through discrimination. From the study, it is concluded that infection with the HIV virus is related to aspects of gender (patriarchy), then the contagion is strongly determined by the type of sexual behavior in every relationship and the number of sexual partners, and finally in terms of the continuity of life, once it has caught the disease, being a carrier of the virus HIV / AIDS is not a condition that limits the continuation of future projects.